Peptide Backbone Modifications - Kazmaier, Uli; Deska, Jan (Current Organic Chemistry, 2008)
The selective introduction or manipulation of side chains in a peptide represents a severe synthetic challenge. During the last years numerous different approaches towards the targeted modification of small to medium-sized peptides have been developed which should be presented in this review. Focusing on the manipulation of the peptide backbone, procedures concerning selective N-alkylation, C-alkylation and Cequals;O-thionation are described.